Postlabeling Methods for Carcinogen-DNA Adduct Analysis - Randerath, Kurt; Randerath, Erika; Agrawal, Hari P.; Gupta, Ramesh C.; Schurdak, Mark E.; Reddy, M. Vijayaraj (Environmental health perspectives, 1985)
Radioactive carcinogens have provided most of our present knowledge about the chemistry of interactions between carcinogens and biological systems. The requirement of radioactive carcinogens has restricted carcinogen-DNA binding studies to chemicals that are readily available in isotopically labeled form, i.e., a minute fraction of all potentially mutagenic or carcinogenic chemicals. To extend the scope of carcinogen-DNA binding studies, an alternative method, which does not require radioactive test chemicals, has been developed. In this approach, radioactivity (32P) is being incorporated into DNA constituents by polynucleotide kinase-catalyzed [32P]phosphate transfer from [γ -32P] ATP after exposure of the DNA in vitro or in vivo to a nonradioactive, covalently binding chemical, and evidence for the alteration of DNA nucleotides is provided by the appearance of extra spots on autoradiograms of thin-layer chromatograms of digests of the chemically modified DNA. Quantitation of adduct levels is accomplished by scintillation counting. The sensitivity of the technique depends on the experimental conditions for32P-labeling and on the chemical structure of the adducts. Greater sensitivity may be achieved if adducts can be separated as a class from the normal nucleotides. This is the case for an estimated 80% of all carcinogens, giving rise to bulky and/or aromatic substituents in DNA. Under the present conditions, one such adduct in 109to 1010normal nucleotides can be detected. A total of approximately 80 compounds has been studied thus far. Binding to DNA of rodent tissues was readily detected by the32P-postlabeling assay for all known carcinogens among these compounds, and adducts were detected in DNA from human placenta of smokers.